INTRODUCTION TO VOLUME 9 : 2011 - Abdullah, Alias (PLANNING MALAYSIA, 2016)
MIP is once again proudly to riposte its ninth volume of Planning Malaysia. Since its inception in 2003, the Journal was well-received by the members as well as the academic fraternity. This is due to perhaps, the awareness for knowledge seeking and improvement among the members as the articles touch on wide spectrum of our daily planning issues. It is indeed a great achievement to the Institute as we strive to encourage more members and academics to write and share new ideas on planning and urban development. As any other professional based publication, one of the main objectives of this journal is to offer a platform for town planners to share ideas and experiences on urban and regional planning matters. These ideas and thoughts may be generated from research, studies undertaken or actual hands-on experiences of planners and academics. MIP hopes the journal can offer a healthier insight to all planners so that their roles as town planners can be meaningfully appreciated by the public and authorities. Apart from the MIP’s contribution to the planning circle, Planning Malaysia is also extended to various planning related organizations, institutions of higher learning as well as to all members of the institute. We anticipate to eventually extending the circulation of this journal to non-planning related organizations and institutions that has an indirect role in planning within and outside the country. We hope this issue will serve the purpose and welcome any feedback for the improvement in the forthcoming issue. As a new preside President, I would like to acknowledge and congratulate the new journal’s Editor-in-Chief, Professor Dato’ Dr. Mansor Ibrahim and his team for the dedication and continuous support to the Institute. Thank you and happy reading.